Biomineralization and Magnetism of Uncultured Magnetotactic Coccus Strain THC‐1 With Non‐chained Magnetosomal Magnetite Nanoparticles. Issue 12 (5th December 2020) - Li, Jinhua; Menguy, Nicolas; Leroy, Eric; Roberts, Andrew P.; Liu, Peiyu; Pan, Yongxin
Abstract: Magnetotactic bacteria (MTB) have long fascinated geologists and biologists because they biomineralize intracellular single domain (SD) magnetite crystals within magnetosomes that are generally organized into single or multiple chains. MTB remains in the geological record (magnetofossils) are ideal magnetic carriers and are used to reconstruct paleomagnetic and paleoenvironmental information. Here we studied the biomineralization and magnetic properties of magnetosomal magnetite produced by uncultured magnetotactic coccus strain THC‐1, isolated from the Tanghe River, China, by combining transmission electron microscope (TEM) and rock magnetic approaches. Our results reveal that THC‐1 produces hexagonal prismatic magnetite single crystals that are elongated along the [111] crystallographic direction. Most of the magnetite crystals within THC‐1 are dispersed without obvious chain assembly. A whole‐cell THC‐1 sample yields a normal SD hysteresis loop and a Verwey transition temperature of 112 K. In contrast to MTB cells with magnetosome chain(s), THC‐1 cells have a teardrop first‐order reversal curve distribution that is indicative of moderate interparticle interactions. Due to the absence of a magnetosome chain, THC‐1 has relatively high values of the difference between the saturation isothermal remanent magnetization (SIRM) below and above the Verwey transition temperature for field‐cooled and zero field‐cooled SIRM curves ( δ FC, δ ZFC ) and a low δ FC / δ ZFC value. Together with previous studies, our results demonstrate that some MTB species/strains can form magnetosomal magnetite without linear chain configurations. Magnetite produced by MTB has diverse magnetic properties, which are distinctive but not necessarily unique compared to other magnetite types. Therefore, combining bulk magnetic measurements and TEM observations remains necessary for identifying magnetofossils in the geological record. Plain Language Summary: Magnetotactic bacteria (MTB) are intriguing because they produce magnetic nanocrystals of magnetite (Fe3 O4 ) or greigite (Fe3 S4 ) within intracellular organelles (magnetosomes) that can leave tiny magnetic fossils (magnetofossils) in the geological record. Magnetofossil identification for paleoenvironmental and paleomagnetic purposes is based heavily on knowledge of modern MTB that often organize magnetic particles into chain(s). We studied here the crystallographic and magnetic properties of uncultured magnetotactic coccus strain THC‐1 in which magnetosomal magnetite particles are dispersed without obvious chain assembly. In contrast to whole‐cell MTB samples with magnetosome chain(s), THC‐1 has distinctive magnetic properties. Together with previous studies, our results demonstrate that MTB magnetite has diverse magnetic properties that are distinctive but not necessarily unique compared to other magnetite types. This indicates that combining magnetic measurements and transmission electron microscope observations remains necessary for identifying magnetofossils. Key Points: Magnetotactic coccus THC‐1 forms prismatic magnetosomal magnetite that is dispersed within the cell THC‐1 has distinctive magnetic properties compared to magnetotactic bacteria (MTB) with magnetosome chains MTB magnetite is magnetically distinctive but not unique compared to other magnetite types